235 Penile Invagination and Corporal Excavation for Penile Prosthesis Placement in Severe Corporal Fibrosis. Issue 1 (1st April 2022) - Kim, C; Campbell, S; Allkanjari, A; Barton, G; Lentz, A
ABSTRACT: Introduction: The penile prosthesis is a standard treatment for men with erectile dysfunction refractory to vacuum, medical, or injection therapies. In patients with virgin tissue planes and normal anatomy, prosthesis placement can be technically straight forward and associated with minimal morbidity. Patients with corporal fibrosis present a unique surgical challenge for implantation and there is no standardized approach to care. Selection of the appropriate surgical technique can vary depending on the extent of corporal fibrosis and surgeon experience. In this case, our patient's corporal fibrosis resulted from two episodes of prolonged priapism as well as two distal shunts and a failed attempt at inflatable penile prosthesis placement resulting in a prolonged wound infection. Objective: We present our unique surgical approach for penile prosthesis implantation in the most severe cases of corporal fibrosis. Methods: Video demonstration of corporal excavation and penile prosthesis placement via a perineal incision with complete penile invagination. Results: Comprehensive pre-operative planning guided our decision to utilize a malleable prosthesis given the severe degree of corporal fibrosis and higher risk of complications with a three-piece IPP. Our penile invagination technique allowed us to achieve complete longitudinal corporal exposure while avoiding multiple incisions or overlapping incisions near the corporotomy and cylinders. Tachosil or other biologic grafts should be available for use in cases where primary corporotomy closure is not possible. Conclusions: We demonstrated that penile invagination, corporal excavation, and implantation with a malleable prosthesis is a safe and effective treatment for patients with the most severe corporal fibrosis. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Coloplast and Boston Scientific